TEACHING RESEARCH: HOW TEACHING EXPERIENCE INSPIRED A NEW METHOD OF SUPERVISION IN LAW - Teixeira, Ana Paula Fernandes; Peres, Anna Paula Lemos Santos; Gabrich, Lara Maia Silva (Seven Editora, 2026)
This study analyzes the combination of active learning methodologies applied at a higher education institution, UNIFIPMoc, during the period from 2007 to 2021, considering a constructivist reinterpretation and the humanization of guidance in terms of the advisor–advisee relationship during the production of the Undergraduate Final Project (UFP), as well as the development of specific procedures for organizing the supervision process. The objective is to highlight the method created for supervising scientific research based on the experience gained through undergraduate thesis supervision in the Law program. This is an experience report resulting from both faculty and student praxis in the production of the Undergraduate Final Project in the Law program at UNIFIPMoc. In this context, the collective writing experience developed here drew on contributions from major scholars of learning methodologies, notably Piaget (1987), Ausubel (2000), Edgar Morin (2015), Novak and Gowin (1996), and Moreira (2011). Among the problems arising from the traditional supervision of scientific work in the Law program, the emergence of a backlog of students in a system marked by dependency and disengagement was observed, as students showed significant difficulty in progressing in the development of their research projects. The encouragement to establish a qualified Core of Academic Advisors contributed to reflection on appropriate supervision procedures developed over time. In pursuit of greater organization and optimization of academic work and supervisory relationships, these procedures, combined with the use of integrated active learning methodologies, proved essential for establishing a humanized approach to student guidance. Together, these initiatives resulted in a proprietary method for supervising undergraduate theses in the Law program at UNIFIPMoc, grounded in the organization of specific supervisory procedures, curriculum restructuring, and the combined use of active learning methodologies. This method fostered the development of scientific research within the Law program despite the challenges related to academic training processes in contemporary society, contributing to the reduction of student backlog in dependency systems, improving approval rates among regular students, and positively influencing the overall quality of undergraduate final projects. DOI: https://doi.org/10.56238/sevened2026.008-082